PENGARUH METODE PEMBELAJARAN MULTISENSORI TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA MATA PELAJARAN BAHASA INDONESIA - Purnamasari, Siska; Mas Ramadhan, Gilang; Krisna, Dede; Hikmah Priananda, Meril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early reading ability is a basic skill that must be mastered by elementary school students as a foundation for acquiring various knowledge at the next level of education. However, there are still students who experience difficulties in early reading so that learning methods are needed that can improve these abilities. This study aims to determine the effect of multisensory learning methods on early reading ability in the Indonesian language subject of second-grade students of Cibeureum State Elementary School. This study uses a quantitative approach with an experimental method and a One Group Pretest-Posttest Design. The research sample consisted of 28 second-grade students of Cibeureum State Elementary School who were determined using Purposive Sampling Technique. Data collection was carried out through an early reading ability test given before treatment (pretest) and after treatment (posttest). Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Paired Sample t-Test hypothesis test. The results showed that the average pretest score of early reading ability was 58.21, while the average posttest score was 85.18. There was an average increase of 26.97 or 46.34% after the implementation of the multisensory learning method. The results of the normality test showed that the pretest and posttest data were normally distributed with significance values ​​of 0.135 and 0.089, respectively (p > 0.05). Furthermore, the results of the Paired Sample t-Test showed a significance value of 0.000 (p < 0.05), so the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected. Based on the results of the study, it can be concluded that the multisensory learning method has a significant effect on the beginning reading ability of second-grade students of Cibeureum State Elementary School. The multisensory learning method has been proven effective in improving beginning reading ability through the involvement of various senses, namely visual, auditory, kinesthetic, and tactile in the learning process.